2011
DOI: 10.2478/v10045-011-0050-8
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils and Trichoderma Harzianum as an Integrated Control Measure Against Faba Bean Root Rot Pathogens

Abstract: Essential Oils andTrichoderma Harzianumas an Integrated Control Measure Against Faba Bean Root Rot PathogensCarnation, caraway, thyme, peppermint and geranium essential oils have been found to have inhibitory effects against the mycelial growth ofFusarium solani,Rhizoctonia solani,Sclerotium rolfsiiandMacrophomina phaseolinaunderin vitroconditions. Complete inhibition of fungal growth was observed with the use of 4% carnation and geranium oils. Mycelial growth of the tested fungi showed more sensitivity to hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 30 publications
6
27
1
2
Order By: Relevance
“…Trichoderma viride and T. harzianum in a pot culture study reduced the collar rot incidence in groundnut caused by A. niger (Gajera et al, 2011). Application of essential oils integration with the bio-agent T. harzianum was found to be suitable, safe and cost-effective for controlling soil borne diseases like Faba bean root rot (Abdel-Kader et al, 2011). Similar observations were recorded with other species of Trichoderma for controlling soil-borne diseases.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Trichoderma viride and T. harzianum in a pot culture study reduced the collar rot incidence in groundnut caused by A. niger (Gajera et al, 2011). Application of essential oils integration with the bio-agent T. harzianum was found to be suitable, safe and cost-effective for controlling soil borne diseases like Faba bean root rot (Abdel-Kader et al, 2011). Similar observations were recorded with other species of Trichoderma for controlling soil-borne diseases.…”
Section: Discussionsupporting
confidence: 66%
“…are widely used in agriculture as biopesticides, bioprotectants, biostimulants, and biofertilizers on a wide variety of plants (Harman & Kubicek, 1998). It has been found from different research works that Trichoderma can reduce the disease incidence caused by Aspergillus niger (Gajera et al, 2011;Rajkonda et al, 2011), Aspergillus flavus (Reddy et al, 2009), Sclerotium rolfsii (Abdel-Kader et al, 2011;Manjula et al, 2004), Pythium aphanidermatum (Devaki et al, 1992;Sharma & Sain, 2003, 2006Mishra, 2010), Rhizoctonia solanii (Abdel-Kader et al, 2011;Gveroska & Ziberoski, 2011). Both T. viride and T. harzianum were found to be capable of reducing the sclerotial population of M. phaseolina (Sharma, 1982;Sharma & Dureja, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It is infested with many fungal pathogens causing considerable yield losses where dampingoff, root-rot, wilted diseases affecting faba bean production in Egypt Abdel- Kader et al, (2011). In this study induced resistance against root-rot were shown when intercropping and fertilization also decreased the fungal growth of R. soloni in vivo.…”
Section: Effect Of Intercropping Three Cultivars Of Faba Bean With Whmentioning
confidence: 61%
“…Danas postoji sve veće interesovanje za etarskim uljima kao mogućoj zameni za konvencionalne sintetičke fungicide u cilju zaštite kultivisanih biljaka od fitopatogenih gljiva, zbog njihove opšte prihvaćenosti od potrošača, relativne bezbednosti za upotrebu i ekološke prihvatljivosti [34]. Literaturni podaci ukazuju na efikasnost i primenu kako etarskih ulja, tako i izolata roda Bacillus u zaštiti povrtarskih biljaka od strane fitopatogenih gljiva, tretmanom zemljišta u kome će biljka rasti, tretiranjem korena biljaka i/ili prskanjem listova [34,35] ili tretmanom etarskim uljima u prevenciji suzbijanja fungalnih infekcija semena [36].…”
Section: Tabela 3 Fic I Fici Vrednosti Ekstrakata U Različitim Kombiunclassified
“…Tako je kombinacijom B. amyloliquefacijens i etarskog ulja limunske trave (Cymbopogon citrates) postignut izostanak fitopatogenih oboljenja na skladištenim breskvama sinergističkim dejstvom ovih bioloških agenasa [35]. Takođe, visoka efikasnost u prevenciji kontaminacije patogenim gljivama povrtarskih biljaka postignuta je integrisanim tretmanom zemlje kombinacijom gljive antagoniste i odabranih etarskih ulja, poput kima, timijana, nane i geranijuma [34]. Sinergizam u antifungalnoj aktivnosti lipopeptidnog ekstrakta i etarskih ulja može se tražiti u hemijskoj strukturi ovih agenasa i aktivnosti usmerenoj ka citoplazmatičnoj membrani.…”
Section: Tabela 3 Fic I Fici Vrednosti Ekstrakata U Različitim Kombiunclassified